Dust particle deposition quality assessment in rural areas located not far from a congested highway and several sebkhas: case of Monastir region, Eastern Tunisia - Chabbi, Iness; Bahloul, Moez; Dammak, Rim; Azri, Chafai (Journal of Environmental Engineering and Landscape Management, 2018)
In order to better understand the processes of removing atmospheric particles to the surface, dry particle deposition in Monastir region (eastern Tunisia) has been studied. As a first step, a biweekly monitoring of the particulate deposits was carried out in 26 sites from January to August, 2012. Secondly, two particular sites were investigated from October, 2014 to August, 2015. A very high fluctuation in those particle fluxes, ranging from 0.560 to 2.210 g/m2/14days, was clearly observed. The spatial distribution of particulate deposits shows a growing trend from rural to urban (coastal) areas depending on nearby sources (brickyards and clay quarries, road traffic and sebkhas) and meteorological factors (including precipitation and wind speed). The combined geochemical-statistical study of the particulate deposits elementary fluxes (Cl-, Na+, K+, Ca++, Fe(2,3)+, Cd, Pb, Zn, Ni, Mn and Cu) at the two observed rural and urban sites show a non-negligible impact of the anthropogenic component attributed to metals (Pb, Mn, Zn, and Cu). It is linked to the simultaneous effect of the urban (mainly road) activities in the Eastern part of the region and the intense fluidity of the motorway and railway in its Western part. The importance of the chlorine contributions of the terrigenous circulation has been attributed to the effect of sebkhas. The phenomenon of dust resuspension in agricultural areas, clay storage near brickyards and unbuilt sites has also been highlighted. The lowest biweekly elementary fluxes are probably due to the effect of rainfall periods which causes atmospheric whash-out.